Changes of the lysozyme level in the serum and organs of the aging rats - Trajkov, D; Jurhar Pavlova, M; Petlichkovski, A; Pavkovic, M; Spiroski, M ("Ss Cyril and Methodius"University, Faculty of Medicine, Skopje, Institute for Immunology, 1997)
The enzyme lysozyme or muramidase (E.C.3.2.2.17) catalyzes the hydrolysis 1,4-b glycoside linkages between N-acetylmuraminic acid and N-acetyl glucosamine in peptidoglycans. Lysozyme is part of the congenital immunity and has bactericide activity maily on gram (+) bacteria, although there is evidence of his activity on gram (-) bacteria, too. Lysozyme catalyzes not only the breakdown of the peptidoglucan from the bacterial wall, but it also influences on the complement as well as on the synthesis of the antibodies. The aim of this paper was to find out the changes in the activity of lysozyme during the process of aging. The investigation was performed on 68 male Wistar rats divided into 6 groups. The first group (n=13) was 1 month old, the second (n=13) was 3 months old, the third (n=11) 6 months, fourt (n=12) 9 months, the fifth (n=12) 12 months and the sixt (n=7) was 18months old.The lysozyme activity was examined in the serum and organs on lysoplates modifided for our conditions. The analyses have shown that the present changes in the lysozyme activity in the epididymis, mesenterium and testis are not statisticaly significant. The activity of lysozyme in te serum is significantly increased (p<0.005) in the second group whereas in the spleen (p<0.01) and in the kidney (p<0.001)it was higher in the fourth group. Lysozyme showed significant increase (p<0.007) in the lungs in the second and fourth group and in the thymus in the fifth group (p<0.001). The results have shown that the process of the aging has influenced on the lysozyme activity in certain tissues. This activity is increased and is very apparent in the serum as early as in third month, whereas in the other tissues it appears in the ninth month.Thera are still no reliable data for the appearance of these changes, but there is no mutual mechanism for all of them.